Sensitivity of dynamical systems to parameters in a convex subset of a topological vector space - H.T. Banks; S. Dediu; H.K. Nguyen (Mathematical Biosciences and Engineering)
We develop a theory for sensitivity with respect to parameters ina convex subset of a topological vector space of dynamical systemsin a Banach space. Specific motivating examples for probabilitymeasure dependent differential, partial differential and delaydifferential equations are given. Schemes that approximate themeasures in the Prohorov sense are illustrated with numericalsimulations for distributed delay differential equations.